Conceptual framework of organizational knowledge management capabilities - Yasin, Ida; Jemain, Abdul Aziz; Abdullah, Mokhtar (2004)
Various efforts were attempted by companies to deploy knowledge management.The quest to move beyond information management and into the realm o undertaking involving the development of the structures of the firm.Therefore, the identification and assessment of precondition is necessary for the organization to have successful knowledge management initiatives.The paper provides a theoretical framework on assessing the capability of an organization towards successful knowledge management.The framework providestwo dimensions of organizational capabilities namely socio-technical and processes.Then, it leads to organizational effectiveness, and finally, leads to organizational performance.